Pemahaman Konsep Mahasiswa Semester Satu pada Mata Kuliah Trigonometri - Mustangin, Mustangin; Setiawan, Yayan Eryk (Universitas Hamzanwadi, 2021)
Trigonometry, a discipline in mathematics, is often misunderstood by mathematics learners. To understand Trigonometry, students should start learning from understanding Mathematical concepts. Therefore, this study aims to analyze students' understanding of concepts in the Trigonometry course. This research is a qualitative descriptive study of the first semester students' conceptual understanding of the mathematics education study program at a university in Malang City. The data collected in this study consisted of the subject's work and transcripts of interviews. The instrument used in this study consisted of 6 questions about understanding the concept of trigonometric material. Analysis of the subject's work results is carried out to find out the right or wrong answers. Meanwhile, the interview transcripts were analyzed by coding to determine the factors that support conceptual understanding. The results showed that students with good conceptual understanding could solve trigonometric problems, while students with less understanding of concepts had difficulty solving trigonometric problems. The results of this study also found aspects that influence (encourage and inhibit) students in understanding the concept of trigonometry. Furthermore, this research is expected to contribute to trigonometry subjects' learning based on indicators of conceptual understanding in the Trigonometry course.